Geochemistry of suspended material and sediments in boreal lakes - Peinerud, Elsa (Luleå tekniska universitet, 2000)
The geochemistry of suspended material and sediment has been studied in four boreal lakes: Lakes Kutsasjärvi, Sakajärvi, and Ala Lombolo in northern Sweden and Lake Imandra on the Kola Peninsula, Russia. Suspended material and filtered water have been sampled in time series and depth profiles. The suspended material is collected on filters, which are dissolved and analyzed. Sediment cores from all lakes are taken. Major and trace element analyses are mainly performed by ICP–QMS and ICP–AES. The main theme in this thesis is the relation between the suspended material and the sediment, and the geochemical cycling of elements within the lakes. In this context, processes like biological production and decomposition, and precipitation and dissolution of inorganic phases are important. Special attention is paid to redox processes of Fe and Mn, and to the implications of these processes. A thorough discussion of diatom Si in sediments and suspended material is also included. The high concentrations of organic material and diatom Si in the water column of Lake Kutsasjärvi during summer dilutes most other components, rendering these concentrations lower in the suspended material than in the sediment. The non-detrital fractions (i.e., the fraction that is not related to primary mineral particles) of all major elements are, however, higher in the suspended material, partly as a consequence of higher dissolution rates of diatom Si and non-detrital Fe and Mn in the sediment, but also because no sampling of suspended material was performed during spring-flood, when the inflow of detrital particles (i.e., minerogenic particles deriving from the mechanical weathering of rocks) is probably highest. Like the major elements, most trace elements show higher concentrations in the sediment than in the suspended matter. The enrichment of trace elements in the suspended material, compared with detrital particles, is, however, higher. During winter, when Lake Kutsasjärvi is ice-covered, the redox cycle of Fe is a dominant process in the ...